Joachim von Watt (Vadian): Aequivoca nomina christiana ad religionem pertinentia - Stettler, Bernhard (Zwingliana, 2017)
This paper presents a treatise of Joachim Vadian entitled "Aequivoca nomina christiana ad religionem pertinentia" (Christian terminology with equivocal meanings) which exists only in a handwritten version. Vadian’s undertaking was obviously influenced by Erasmus, who already criticized in his "Enchiridion militis Christiani" (1503) the fact that some theological terms or concepts were used wrongly in the course of time and gradually shifted towards other meanings no longer compatible with their original use in the New Testament and the Old Church. The manuscript as we know it today was expanded in the 1540s. Vadian may have been prompted to this work after having expanded and revised Christoph Schappeler’s treatise on Prayer in the early 1540s. Yet a close study of the "Aequivoca Nomina" also reveals that for some of the concepts he discussed Vadian used notes he had written in the 1520s and 1530s. Vadian’s interest in theology has long been known and reveals itself in his treatise on the Eucharist (1536) and in his polemical tracts against Kaspar von Schwenckfeld, in one of which the two natures of Christ (1540) were examined. It is now possible to state that Vadian was not only interested in theological matters, but that he also grappled with theological issues more than was previously assumed. Indeed, a study of the "Aequivoca Nomina" allows the conclusion that he read Peter Lombard, Gratian’s compilations of legal texts, the “Summa” of Thomas Aquinas, quite a large number of patristic sources and numerous writings of Erasmus (e.g. the "Paraphrases"), which he used without explicitly referring to their authors.